Wisdom, science and the scriptures: essays in honour of Ernest Lucas - Finamore, Stephen; Lucas, Ernest (Centre for Baptist History and Heritage, Regent's Park College, 2012)
Wisdom in the Bible -- Science and Christian faith -- The scriptures -- ...and cricket